2007
DOI: 10.1212/01.wnl.0000266670.35219.0c
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective effects of caffeine

Abstract: The psychostimulant properties of caffeine appear to reduce cognitive decline in women without dementia, especially at higher ages. Although no impact is observed on dementia incidence, further studies are required to ascertain whether caffeine may nonetheless be of potential use in prolonging the period of mild cognitive impairment in women prior to a diagnosis of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
267
3
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(291 citation statements)
references
References 24 publications
16
267
3
5
Order By: Relevance
“…Fasting blood samples were taken at baseline for lipid and glucose levels and APOE4 genotyping (Ritchie et al, 2007). History of ischemic pathologies (stroke, angina pectoris, myocardial infarction and cardio-vascular surgery) was established according to standardized questions.…”
Section: Socio-demographic and Clinical Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fasting blood samples were taken at baseline for lipid and glucose levels and APOE4 genotyping (Ritchie et al, 2007). History of ischemic pathologies (stroke, angina pectoris, myocardial infarction and cardio-vascular surgery) was established according to standardized questions.…”
Section: Socio-demographic and Clinical Variablesmentioning
confidence: 99%
“…Multivariate adjusted logistic regression further included covariates associated with cognitive decline (at p<0.15); depression, diabetes, hypercholesterolemia, caffeine, smoking, APOE4, ischemic pathologies, chronic joint or back pain, bronchitis, asthma and other chronic respiratory disorders. Due to the skewed distribution of cognitive scores, a substantial decline in cognitive function over follow-up was defined as the lowest quintile of the difference between either follow-up visit and baseline score except for response time recorded for the TMT, for which the highest quintile of the difference was considered (Ritchie et al, 2007). We also used random-effect models to analyze the association between CS use and 7-year change on cognitive scores taken as continuous variables.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Eskelinen et al (2009) reported a 65 % risk reduction for late-life dementia and AD among drinkers of three to five cups of coffee per day during their middle life, compared with nondrinkers. The caffeine in coffee has been implicated as the active component associated with risk reduction of cognitive decline and dementia among coffee drinkers (Maia and de Mendonca 2002;van Gelder et al 2007), particularly among women (Ritchie et al 2007;Santos et al 2010). However, coffee also contains a variety of other bioavailable and potentially therapeutic phytochemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Human epidemiological and animal experimentation studies as well as studies conducted in cultured cell models have shown that caffeine protects against the onset and severity of AD [19][20][21][22][23][24][25][26][27][28]. Additionally, it has been shown that it can reverse behavioral and pathological features of AD [19,21,22,24,25,[29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been shown that it can reverse behavioral and pathological features of AD [19,21,22,24,25,[29][30][31][32][33]. Importantly, these protective effects of caffeine are observed using pharmacologically relevant doses [28,34].…”
Section: Introductionmentioning
confidence: 99%